2023
DOI: 10.1017/s0022149x23000111
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of trematode parasite infectious stages: from conceptual synthesis to future research agenda

Abstract: Given their sheer cumulative biomass and ubiquitous presence, parasites are increasingly recognized as essential components of most food webs. Beyond their influence as consumers of host tissue, many parasites also have free-living infectious stages that may be ingested by non-host organisms, with implications for energy and nutrient transfer, as well as for pathogen transmission and infectious disease dynamics. This has been particularly well-documented for the cercaria free-living stage of digenean trematode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 124 publications
0
9
0
Order By: Relevance
“…The effect of temperature may be clear-cut in the latter, but obscured by confounding factors in nature. One of these confounding factors may be predation on cercariae by non-host organisms (Johnson et al 2010 ; Mironova et al 2020 ; Koprivnikar et al 2023 ), which may intensify at high summer temperatures (e.g., Goedknegt et al 2015 ) and offset the higher output of cercariae from first intermediate hosts (but see Gopko et al 2020 ). Another possibility is that parasite-induced mortality may be exacerbated by higher temperatures, leading to the disappearance of the more heavily infected second intermediate hosts (see Gordon and Rau 1982 ; Rousset et al 1996 ; Fredensborg et al 2004 ) and thus lowering observed mean abundance of infection in summer.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of temperature may be clear-cut in the latter, but obscured by confounding factors in nature. One of these confounding factors may be predation on cercariae by non-host organisms (Johnson et al 2010 ; Mironova et al 2020 ; Koprivnikar et al 2023 ), which may intensify at high summer temperatures (e.g., Goedknegt et al 2015 ) and offset the higher output of cercariae from first intermediate hosts (but see Gopko et al 2020 ). Another possibility is that parasite-induced mortality may be exacerbated by higher temperatures, leading to the disappearance of the more heavily infected second intermediate hosts (see Gordon and Rau 1982 ; Rousset et al 1996 ; Fredensborg et al 2004 ) and thus lowering observed mean abundance of infection in summer.…”
Section: Discussionmentioning
confidence: 99%
“…We also considered identified predator–parasite links in previously published food webs (Thieltges et al 2011 ; Zander et al 2011 ; Mouritsen et al 2011 ; Preston et al 2012 ). Links identified from the literature were included in the current food web based on the predators’ ability to feed on small-sized organisms, such as ciliates and other protozoans, combined with known or measured size of the free-living parasitic stages of the parasite species in question, while also considering their typical habitat affiliation and behavior (i.e., Lafferty et al 2006a , b ; Orlofske et al 2015 ; see also Koprivnikar et al 2023 ). Five of these links (between stickleback/amphipods and three species of trematode cercariae) have later been confirmed in Takvatn by experimental studies (Born-Torrijos et al 2020 , 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most of this work has been conducted with free-living cercarial stages of trematodes that infect tadpoles and it has indicated that less competent hosts can act as decoys for infective stages, thereby lowering infection levels in the main competent host (Johnson et al 2008a , 2013 ). Finally, a third line of research has been focussing on how non-hosts (i.e., organisms which do not serve as competent host or less competent decoys and thus do not become infected) can interfere with the transmission of free-living infective stages (Thieltges et al 2008 ; Johnson and Thieltges 2010 ; Koprivnikar et al 2023 ). This interference can, for example, occur when non-hosts prey on free-living infective stages or act as a physical obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in aquatic environments, where vectors are much less common than on land and where transmission of parasites and pathogens mainly occurs via the water column, ‘pathogen filtration’ by non-hosts in form of physical obstructions by vegetation or filter feeding removal by bivalve beds has received increased interest as a potential ecosystem service and disease managing approach (Burge et al 2016 ; Lamb et al 2017 ; Klohmann and Padilla-Gamiño 2022 ). However, non-host species differ in their capability to consume or obstruct infective stages depending on the specific parasites or pathogens in question and some non-host species may not show an effect at all (e.g., Hopper et al 2008 ; Orlofske et al 2015 ; Welsh et al 2014 , 2020 ; Koprivnikar et al 2023 ). Non-hosts that do consume or physically obstruct infective stages usually do so in a density-dependent fashion, i.e., the effect increases with non-host density (Thieltges et al 2009 ; Rohr et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%